Implementasi Algoritma Apriori Untuk Pola Pembelian Bundling Pada UMKM Berbasis Website - Fahriza Hasibuan, Alya putri; Triase, Triase (JURNAL RISET KOMPUTER (JURIKOM), 2025)
The rapid development of the digital era encourages the utilization of information technology to enhance the efficiency and competitiveness of MSMEs, including Bumie Belepot. Problems in the sales system, which is still manual and lacks a bundling feature, have led to unstable transactions and long queues. This study aims to develop a website-based system that applies bundling strategies to increase the number of transactions and improve customer satisfaction. The Apriori method is used to analyze customer purchasing patterns based on transaction data from January 2024 to January 2025, with a minimum support threshold of 60%. The analysis results identified five itemset 3 combinations with strong correlations between menu items, such as Bumie Belepot – Mie Ayam Bakar – Lemon Tea and Mie Ayam Bakar – Teh Manis – Lemon Tea, which are considered potential bundling options. Unlike previous studies, this research not only focuses on analyzing association patterns but also develops a website-based system equipped with bundling features, order management, and sales data reports. The system design utilizes UML modeling to describe the website's structure and workflow in detail. With this approach, the research is expected to improve operational efficiency, customer satisfaction, and the competitiveness of Bumie Belepot in the culinary industry.